Pengaruh Variasi Temperatur dan Derajat Keasaman (pH) Air Pencucian Pada Aktivasi Zeolit Pelet Terhadap Prestasi Mesin Diesel 4-Langkah - Pandapotan, Chandra Winata; Wardono, Herry (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
One of efforts to save fuel consumption can be done by using thermal-acid activated zeolite as adsorbent for water vapor and nitrogen. Herry Wardono has proved that the value of concentration of 0.3 N and 0.5 N in the chemical activation can save specific fuel consumption. The best result occurred in the use of thermal-chemical activated zeolite. In this research, thermal activation temperatures used were 150 0C and 200 0C respectively for 1 hour. Variations of washing water pH were also performed on the 4.5, 5.5 and 7. The results showed this thermal activation of 200 0C on activator HSO24 0.3 N and HCl 0.3 N can save fuel by 5.350% and 7.811% respectively. Then the pH value of 7 gave the best fuel consumption savings those were of 5.964 % and 7.175% for use of HSO 0.5N24 and HCl 0.5N. This result occured at low speed (1500 rpm).Keywords : adhesive pelletize zeolite, thermal activation, effect of washing water pH